New Record of Marine Parasitic Isopods (Family, Corallinidae) from South Andaman, Andaman Islands, India - Anil, Pathan; Das, Tarun; Jayaraj, Kaderambil Arjunan (Journal of Tropical Life Science, 2018)
Parasitic isopods are causing problems to the worldwide fishery resources. The studies on parasitic isopods are very scanty in Andaman Islands. So here we provided information on the distribution of two species of parasitic isopods of fishes from Junghlighat fish landing center of South Andaman. The two marine parasitic isopods species are Argathona rhinoceros (Bleeker 1857) and Argathon amacronema (Bleeker 1857). They found to infest the host marine fishes Epinephelus coioides (Hamilton 1822) and Epinephelus tauvina (Forsskal 1775) respectively. These two species were collected from the nostril cavity of the individual host fishes. The morphological characteristics of two specimens are described in detail. Prevalence of corallinids provides additional information to update the check list of isopods from Andaman and Nicobar Islands.